Characterization of slotted photonic crystal waveguide and its application in nonlinear optics. (September 2017) - Datta, Tanmoy; Sen, Mrinal
Abstract: Characteristics of slotted photonic crystal waveguides (SPCWs) are highly dependent on width and refractive index of the slot. This dependence has been explored in this paper, by calculating the respective dispersion diagrams using the three-dimensional full-vector Plane Wave Expansion method. Group index and effective modal area of the SPCWs have been calculated, subjected to these variations, to characterize its slow light performance and confinement respectively. The results are expressed as a function of normalized frequency and, hence, can characterize a SPCW of arbitrary scale and operating wavelength of interest. The analysis presented in this paper is able to save a significant computation time of the researchers working in this domain. Finally, the enhancement of the stimulated Raman scattering (SRS) has been analysed in a SPCW, to characterize its nonlinear performance, by using a low-index highly nonlinear material in the slot. A net gain of the order of 11 dB is found in a ∼7 μm long SPCW. Highlights: Variation of characteristics of slotted photonic crystal waveguides (SPCWs) on slot width and index is presented. Scale invariant and frequency scalable values of group index and the modal area of the SPCWs are obtained. The results show sufficient corroborations with that of the experimentally measured values. Stimulated Raman scattering inside the SPCW has been investigated to demonstrate its application in nonlinear optics. The analyses presented would save intensive-computation time of the researchers working in this domain.